Behind the green card : how immigration policy is killing the American dream - Dobkin, Donald S. (Algora Publishing, 2013)
Behind the Green Card explodes the innumerable myths and bogeymen that obscure the reality of US immigration policy. Blinded by misguided 'national security interests, ' the United States has codified a series of unworkable and irresponsible laws which make this country weaker, poorer and less secure than ever. Through the elimination of both a huge marketplace and enormous supply of labor, the US struggles to regain economic growth while other developed nations, through sensible immigration policies, forge ahead.